Hakikat Peserta Didik dalam Sistem Pendidikan Islam di MAS AL-WASHLIYAH 22 TEMBUNG - Tika Kesuma Wardani; Uswatun Hasanah; Muhammad Iqbal Nasution; Farhan Pulungan; Inom Nasution (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
This research aims to examine the nature of students in the Islamic education system from a theoretical perspective. The author explains things to find out what students mean, what are the criteria for good and correct students, what is the role of teachers towards students, and teaching methodology what is effective for students and the rights and responsibilities of students. This study uses a qualitative method. The author also always writes down the results of interviews addressed to WKM MAS AL-WASHLIYAH 22 TEMBUNG in each of the titles we have mentioned. The author also presents several learning methods that can be used by teachers.